Knowledge, attitude and practice of urticaria patients towards urticaria medication treatment: a cross-sectional study at the first affiliated hospital of Kunming Medical University - Weijia Zhao (BMJ Open)
Objectives To explore the knowledge, attitudes and practices (KAP) of urticaria patients regarding the medication treatment.Methods design A cross-sectional study.Setting At the Dermatology Department of the First Affiliated Hospital of Kunming Medical University from 15 June 2023 to 12 March 2024.Participants Urticaria patients.Primary and secondary outcome measures The primary outcome was KAP of urticaria patients using a self-administered questionnaire. The secondary outcomes were factors associated with KAP.Results A total of 497 valid responses were collected. Of these respondents, 333 (67.0%) were female, and 375 (75.5%) lived in urban areas. The median KAP scores were 1.00 [0.00, 3.00] (possible range: 0–8), 23.00 [18.00, 26.00] (possible range: 10–50) and 32.00 [31.00, 36.00] (possible range: 8–40), respectively. Most patients (91.7%) clearly needed to understand the aetiology and treatment process related to urticaria. Less than half (43.5%) of patients believed that their healthcare providers offered comprehensive information about the knowledge and procedures related to urticaria medication. Demographic analysis uncovered substantial variations in knowledge and attitude scores across different education levels, age groups, occupations and residential areas (p<0.001 for all). In contrast, the impact on practice scores was less significant, particularly concerning educational diversity. Multivariate logistic regression analysis revealed that a higher knowledge score (OR=1.17, 95% CI: [1.03 to 1.33], p=0.014) and age between 35–65 years (OR=1.78, 95% CI: [1.16 to 2.74], p=0.009) were independently associated with proactive practices.Conclusion Urticaria patients exhibit insufficient knowledge, unfavourable attitudes and proactive practices concerning medication treatment. Enhancing patient education and targeted interventions are essential to improve the knowledge and attitudes towards medication treatment, ultimately promoting better self-management practices among urticaria patients.